问题 解答题
1
7
+
2
9
+
4
7
+
7
9
6
7
-(
1
6
-
1
12
9
19
-(
8
9
-
10
19
8
15
+
1
3
-
8
15
4
9
-
2
5
+
5
9
-
2
5
8
9
+
1
6
-
3
4
答案

(1)

1
7
+
2
9
+
4
7
+
7
9

=(

1
7
+
4
7
)+(
2
9
+
7
9
),

=

5
7
+1,

=1

5
7

(2)

6
7
-(
1
6
-
1
12

=

6
7
-
1
12

=

65
84

(3)

9
19
-(
8
9
-
10
19

=

9
19
+
10
19
-
8
9

=1-

8
9

=

1
9

(4)

8
15
+
1
3
-
8
15

=

8
15
-
8
15
+
1
3

=

1
3

(5)

4
9
-
2
5
+
5
9
-
2
5

=(

4
9
+
5
9
)-(
2
5
+
2
5
),

=1-

4
5

=

1
5

(6)

8
9
+
1
6
-
3
4

=

19
18
-
3
4

=

11
36

选择题
单项选择题